توظيف الباحثين الدائمين ضمن نظام الوظيفة العمومية في مراكز البحث - ديدوش، محمد مخطار Didoush, Mohammed Makhtar; داودي، أحمد; بن يطو، أسامة Bin Yatto, Osamah (جامعة قاصدي مرباح ورقلة - كلية الحقوق والعلوم السياسية, 2023)
تتمحور عملية مراكز البحث في الجزائر حول توظيف الكوادر البشرية المؤهلة في التنظيم الداخلي للبحث، ويتركز اهتمامها على السبل الجيدة للاستثمار فيها لضمان استمرارية الأداء من خلال توظيف موارد بشرية كفؤة. ومن الوسائل المهمة لتحقيق ذلك اعتمادها على تطبيق قوانين خاصة للباحثين الدائمين في عملية جذب العنصر البشري لتحقيق الأهداف. تبدأ هذه الجهود بإعلام الجمهور بالوظائف الشاغرة من خلال استغلال وسائل الاتصال المختلفة بين العاملين في المؤسسة وحاملي الشهادات العليا، مما يسهل عملية التواصل بينهم وبين الباحثين عن عمل. The process of research centers in Algeria centered on the recruitment of qualified human resources in the internal organization of research, and its attention is focused on the good ways of investment in them to ensure Continuity of performance through the recruitment of efficient human resources. One of the important means to achieve this is its reliance on the application of special laws for permanent researchers in the process of attracting the human element, to achieve goals. These efforts start by informing the public of vacant jobs by exploiting various tools of communication between employees in the institution and holders of higher degrees certificates, which facilitates the communication process between them and job seekers.
Keywords: مراكز البحث -- التوظيف -- الباحثين الدائمين -- الوظائف العامة -- الجزائر